Media Framing of Socio-Political Discourse in Nigeria - Okuchemiya Success; Carol Dixon Odoyi; Abdullahi Aliyu Maiwada (Britain International for Academic Research (BIAR-Publisher), 2026)
Media framing plays a significant role in shaping public understanding of socio-political issues by influencing how events, actors, policies, and national debates are selected, presented, and interpreted. In Nigeria, where the media operates within a complex socio-political environment characterised by ethnic, religious, economic, and ideological divisions, the framing of public discourse has important implications for citizens' perceptions and democratic engagement. This study examines the framing of socio-political discourse in Nigeria, with particular attention to how the media constructs and represents political and social issues in the public sphere. Anchored in Framing Theory, the study adopts a qualitative research approach based on secondary data. Data are drawn from existing scholarly literature, journal articles, books, media reports, policy documents, and other relevant published sources on media framing and socio-political discourse in Nigeria. The data are reviewed and thematically analysed to identify dominant framing patterns, recurring themes, and the broader implications of media representations for public understanding and democratic discourse. The study argues that media framing extends beyond the presentation of events to influence how audiences interpret political actors, governance, public policies, and societal challenges. It concludes that balanced, responsible, and context-sensitive media framing is essential for promoting informed public debate, democratic participation, social cohesion, and accountable governance in Nigeria.